Positive spaces according to school-aged children in a residential care facility - Olido, Ma. Aniceta Adoracion C.; Sadaya, Jasmine M.; Ugaddan, Miriam I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
Places significantly take part in a childs daily routines and activities. The aspects of these physical locations may also help facilitate the emotions the child may feel towards these areas. This study explored the specific spaces in a residential care facility RCF that evoke positive emotions among the resident children, and the reasons they have for choosing them. The sample consisted of 13 children aged 7 to 10 years old who have been living in the RCF for at least 6 months. Data gathering involves pre-photography and post-photography interviews, as well as photography sessions of the spaces in the RCF by the children. Results reveal that the spaces they photographed are their living quarters, play areas, communal gathering places, locations of institution-related work, learning facilities, and other important areas. Furthermore, it is found that children have five main reasons for determining their positive spaces. Ranked from the most to least frequently mentioned, these are 1. security and belongingness, 2. recreation and entertainment, 3. competence, 4. attainment of physical needs, and 5. aesthetic appreciation. Recommendations for the RCF includes providing personal belongings or spaces for the children and focusing on improving the quality of intra- and interpersonal relationships among the people in the RCF, among others.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman
Keywords: Orphanages -- Institutional care -- Philipines; Children -- Institutional care -- Philippines; Child care services -- Philippines; Play environment -- Philippines